Security as a Determinant of the Preparation of Migration Policy of the Republic of Poland - Polko, Paulina (Roczniki Nauk Społecznych, 2025)
The article aims to analyse the critical determinants of internal security arising from challenges and threats generated by migration movements, along with recommendations for relevant content to be included in the prepared migration policy for the Republic of Poland. The research question addresses the main problem: What examples of solutions used in selected European Union member states can be implemented in the Polish migration policy to ensure the internal security of the Republic of Poland? The study employs the case study method to examine selected migration policies of EU member states created or updated in the third decade of the 21st century, located in various parts of the EU and experiencing a diverse impact (including varying intensity) of migration processes on internal security. The analysis results indicate that in constructing migration policies, the authorities of the Republic of Poland should concentrate on 1) restrictions in the rules clarifying the granting of asylum (international protection); 2) tightening border controls and streamlining the border protection process; 3) streamlining decision-making procedures for pending applications, including return decisions; 4) discouraging permanent residence; 5) directing migration to third countries; and 6) selective policies inspired by labour market needs.